Vicariance of Pyrocoelia fireflies (Coleoptera: Lampyridae) in the Ryukyu islands, Japan. (4th June 2015) - Osozawa, Soichi; Oba, Yuichi; Kwon, Hyeok‐Yeong; Wakabayashi, John
<x xml:space="preserve">Abstract</x> We performed molecular phylogenetic analyses based on the mitochondrial COI gene (687 bp) and the nuclear 28S rRNA gene (715 bp) and reconstructed phylogenetic trees of the Pyrocoelia fireflies in the Ryukyu Islands and eastern Asia. Age calibration was done using a robust geological constraint: the Okinawa trough and associated straits began to rift at 1.55 Ma, isolating the Ryukyu Islands from the Chinese continent, Japanese islands, Taiwan island and some of the islands from each other. We suggest that the physical isolation of these islands began to generate the allopatric speciation within these islands, so the timing of this isolation was assigned to an appropriate node. The topology is completely concordant among phylogenetic trees reconstructed using MEGA (maximum‐likelihood), raxmlGUI (maximum‐likelihood) and BEAST (Bayesian inference; including combined analysis of COI and 28S rRNA genes). Two lineages are recognized, related to their emergence time; spring to summer, and autumn. In each lineage, vicariance is inferred to have begun at 1.55 Ma from our phylogenetic and geological analyses. In lineage 1, P. oshimana (Amami), P. matsumurai (Okinawa), P. discicollis (W. Japan), P. fumosa (E. Japan) and P. abdominalis (Yaeyama) were differentiated. In lineage 2, P. rufa (Tsushima and Korea), P. miyako (Miyako‐jima), P. atripennis (Ishigaki‐jima) and P. praetexta (Taiwan and HongKong) were differentiated. Pyrocoelia analis (Taiwan and China) emerges throughout the year except for winter, and constitutes another lineage. We suggest that Pyrocoelia fireflies differentiated at 2 Ma to generate these three lineages. The base substitution rate for the COI gene is estimated as 4.48% Myr–1 and that for the 28S rRNA gene is 0.394% Myr–1, and these rates were used in a combined BEAty analysis in BEAST.